2022
DOI: 10.1038/s41598-022-14366-9
|View full text |Cite
|
Sign up to set email alerts
|

Universal association between depressive symptoms and social-network structures in the workplace

Abstract: An unhealthy communication structure at a workplace can adversely affect the mental health of employees. However, little is known about the relationship between communication structures in the workplace and the mental health of employees. Here, we evaluated the face-to-face interaction network among employees (N = 449) in a variety of real-world working environments by using wearable devices and investigated the relationship between social network characteristics and depressive symptoms. We found that the cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Notably, the conversations between pairs of individuals within the group reduced their group stress level. There is extensive empirical evidence that stress is in uenced by interpersonal relationships [1][2][3][4][5] , this study is the rst to suggest that interventions in interpersonal relationships can be effective in reducing group stress levels.…”
Section: Impact Of the Interventions In Workplace Behavior On Group S...mentioning
confidence: 97%
See 3 more Smart Citations
“…Notably, the conversations between pairs of individuals within the group reduced their group stress level. There is extensive empirical evidence that stress is in uenced by interpersonal relationships [1][2][3][4][5] , this study is the rst to suggest that interventions in interpersonal relationships can be effective in reducing group stress levels.…”
Section: Impact Of the Interventions In Workplace Behavior On Group S...mentioning
confidence: 97%
“…Further, Lee et al analyzed the network structure of employees using face-to-face communication data from Japanese workplaces obtained with name-tag wearable sensors similar to those used in this study as well as the results of the CES-D 4 . The ndings revealed that the employees with a higher clustering coe cient, which is a measure of the degree to which an individual's immediate contacts are themselves connected, tended to have lower stress levels.…”
Section: Relationship Between Group Stress and Network Structurementioning
confidence: 99%
See 2 more Smart Citations
“…One potential solution to address employees’ declining mental health is the use of emotion-based health assessments, as proposed in the field of affective computing ( 10 , 11 ). Decreased mental health during remote work may be caused partly by a change in the quality of social communication ( 12 , 13 ). In conventional face-to-face communication, managers can realize emotional depression, as a sign of mental health deterioration, through non-verbal information such as tone of voice and facial expression ( 14 ).…”
Section: Introductionmentioning
confidence: 99%